ANALISIS DAYA SAING SEKTOR PARIWISATA KOTA PADANG - Alwi, Farhan; Satrianto, Alpon (Universitas Negeri Padang, 2025)
This study aims to determine the growth of the tourism sector of Padang City compared to the reference area of West Sumatra and to find out what variable indicators are superior in determining the competitiveness of the tourism sector in Padang City, as well as to find out the position of the development of the competitiveness of the tourism sector against its comparative areasThe method used is quantitative. The object of this study is Padang City with Bukittinggi City and Pariaman City as a comparison, the analysis method in this study uses shift share analysis, composite index, and quadrant analysisThe results of this study show that the tourism sector of Padang City is experiencing faster growth and is able to be competitive with the same sector at the provincial level, variable indicators of production factors and demand factors are superior indicators and have good competitiveness for the tourism sector of Padang City, and Padang City is in Quadrant II in the position of the development of the competitiveness of the city's tourism sector Padang with its comparison area.The role of the government and the opportunities that have run effectively should continue to be improved through consistent supervision, advocative policy formulation, and transparent communication. The government is also expected to remain responsive to the needs of the community and conduct periodic evaluations of the programs carried out so that they remain relevant and have a positive impact.